English Language and Literature Teachers on the Integration of Artificial Intelligence in the Philippine Classroom Context - Jaliyah Ashirae S. Peneyra; Ralph Lawrence F. Paras; Shenry Grace B. Tan; Joseph A. Villarama (WISE Pendidikan Indonesia, 2025)
Artificial intelligence (AI) in language education has brought significant changes to the academic system, reshaping the landscape of language teaching and learning, especially how language teachers plan, deliver, and assess their students’ academic journey. This study determined the academic and personal experiences of eight English language and literature teachers on technology integration such as AI and explored the positive and negative influence of integrating AI in teaching and learning. Utilizing a phenomenological qualitative approach, participants were purposively selected and interviewed, guided by 10 open-ended questions. Data were coded and analyzed thematically, revealing key findings: AI for improved teaching and enhanced learning; encountered challenges and risks; ethical concerns; and shifts in teaching strategies and adaptation. Integration of AI in the classroom resulted in a positive impact on teaching and learning English language and literature, depending on critical engagement, responsible use, and teaching strategies to ensure the preservation of essential skills in English language and literature and academic integrity. As AI continues to influence educational practices, teachers play a crucial role in maintaining balance and guiding students to engage critically with AI-generated contents.